Is the waterfall model still relevant today? / Dr. Nur Ida Aniza Rusli - Rusli, Nur Ida Aniza (Universiti Teknologi MARA, Negeri Sembilan, 2022)
Our daily lives have become more dependent on software applications. The use of software applications allows us to automate a variety of processes at home, educational institutions, medical fields and many more. However, if you explore more on software technology, you will find that developing a robust software application involves a lot more than just technical expertise. A software process model can be helpful in this situation. A software process model is an abstract representation of the development process [1]. It helps software development teams outline critical aspects such as the software functionalities, systems flows and the roles of people involved in the software. Many different process models, such as the Waterfall model, the Agile model, and the Spiral model, have been proposed over the years to enhance the quality of software development projects. However, there is no suitable software model that applies to all types of software projects. Therefore, choosing the right software process model is crucial since it may have a significant impact on the quality, usefulness, and development costs of the software project.